Saddam's word : political discourse in Iraq - Bengio, Ofra (Studies in Middle Eastern history (New York, N.Y.), 1998)
By analyzing political terms, concepts, and idioms as used by Saddam Hussein and the Ba'th regime, author Ofra Bengio illuminates Iraq's political culture and the events that these expressions have both reflected and shaped.